The Effectiveness of Online Learning on Buru State High School Students on Learning Achievement in Covid-19 Situation - Muhammad Sayamsudin Sofie; Risman Iye; Fithriyah Inda Nur Abida; Riki Bugis; Musyawir Musyawir; Yulismayanti Yulismayanti (Hasanuddin University, 2022)
The Covid-19 virus has impacted almost every element of human life. Various official actions, especially those taken by the Indonesian government, have been taken to break the chain of transmission of the virus. One of the sectors that will determine the condition of this pandemic is the education of elementary school children. So far, the Ministry of Education and Culture has not urged local governments to open schools outside the yellow and green zones. The purpose of this research is to find out the effectiveness of online learning for high school students in Buru State on learning achievement in the Covid-19 situation. This study uses a combination of quantitative and qualitative research. Quantitative research was conducted to see the level of student learning effectiveness. Qualitative research was conducted to determine student responses to the implementation of learning from home. This is done equally, not too dominant in one of them. Data collection techniques used is a questionnaire using a questionnaire via a google form that is given to students once a month to get an overview of the implementation of online learning during that month. The data analysis technique used is data reduction, data presentation, conclusion drawing drawing/verification. The results of the study indicate that the low learning achievement of students caused by bold learning has made the parties redevelop the applied learning process and increase the intensity of learning so that students experience increased achievement.